2013
DOI: 10.1002/cphc.201300820
|View full text |Cite
|
Sign up to set email alerts
|

Carbamate Stabilities of Sterically Hindered Amines from Quantum Chemical Methods: Relevance for CO2 Capture

Abstract: The influence of electronic and steric effects on the stabilities of carbamates formed from the reaction of CO2 with a wide range of alkanolamines was investigated by quantum chemical methods. For the calculations, B3LYP, M11-L, MP2, and spin-component-scaled MP2 (SCS-MP2) methods were used, coupled with SMD and SM8 solvation models. A reduction in carbamate stability leads to an increased CO2 absorption capacity of the amine and a reduction of the energy required for solvent regeneration. Important factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…A relatively poor correlation ( R 2 =0.89) was observed between the experimental p K a values and those calculated by using SMD/M11L, which prompted us to use the combination of SMD/SCS‐MP2 to calculate the carbamate stabilities of substituted piperazines discussed in the Section 2.2. This superiority of SCS‐MP2 over M11L is in agreement with previous findings on alkanolamines 7c. The base strength of the amine (p K a ) influences the affinity of the amine to react with CO 2 ; the higher the p K a value of the amine, the faster the reaction rate with CO 2 21.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A relatively poor correlation ( R 2 =0.89) was observed between the experimental p K a values and those calculated by using SMD/M11L, which prompted us to use the combination of SMD/SCS‐MP2 to calculate the carbamate stabilities of substituted piperazines discussed in the Section 2.2. This superiority of SCS‐MP2 over M11L is in agreement with previous findings on alkanolamines 7c. The base strength of the amine (p K a ) influences the affinity of the amine to react with CO 2 ; the higher the p K a value of the amine, the faster the reaction rate with CO 2 21.…”
Section: Resultssupporting
confidence: 91%
“…The decrease in carbamate stability of substituted piperazines somewhat parallels an increase in NC bond lengths of the carbamates of the substituted piperazines (see Table 3 and Figure S5 in the Supporting Information). The NC bond length in the carbamate of unsubstituted 1 is 1.471 Å, which is longer than the NC bond length in the carbamate of the industrially used solvent MEA (1.443 Å) 7c. In agreement with this, the carbamate stability (Δ G cs ) for 1 (4.13 kcal mol −1 ) is significantly lower than the Δ G cs of MEA, which is 5.83 kcal mol −1 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The highest NPA charge on the NH moiety was found for N ‐isopropylMEA ( 7 ), which is around −0.39 and followed by −0.38 and −0.37 for N ‐ethylMEA ( 6 ) and N ‐methylMEA ( 5 ), respectively. Furthermore, our previous studies showed that N ‐alkyl‐substituted MEAs form less stable carbamates than unsubstituted MEA 12b. This leads to an increase in the free amine concentration in solution, and thus to higher CO 2 absorption capacities.…”
Section: Resultsmentioning
confidence: 98%
“…63 Further investigation of the carbamate stability on the surface was done using ADMPMD calculations. This charge transfer from the surface reveals that the N doped zinc oxide is a more powerful Lewis base than pure zinc oxide.…”
Section: Co 2 Adsorption On Zn 18 O 17 :Nmentioning
confidence: 99%